The ‘lawnification’ of Australia’s eastern grassy woodlands: the past, current and likely future spread of an invasive perennial grass, Bothriochloa pertusa - Gabrielle Lebbink; Rod Fensham (Biological Invasions, 2023)
Many of today’s damaging invasive plants were intentionally introduced for pasture development and amenity. By examining the introduction history and consequent spread of these species, we can identify factors associated with their successful establishment and dominance. Using collated presence/absence and cover data, alongside a review of the literature and discussions with land managers, we present a comprehensive analysis of the introduction history and spread of the environmental and agricultural grassy weed, Bothriochloa pertusa (L.) A.Camus (Indian couch) throughout Queensland, Australia. Using this data, we also perform habitat suitability models to predict its potential distribution and local-scale cover across Queensland in relation to key environmental variables. We found that B. pertusa was introduced on multiple occasions and across a large area of Queensland, despite re-occurring doubts and poor evidence for its benefit to livestock production. Livestock grazing, associated disturbances (i.e. land clearing, soil erosion) and climatic extremes were commonly associated with its spread throughout the landscape. In 2020 the main area of B. pertusa invasion as indicated by occurrence records spanned 28,537,600 ha. Results from the habitat suitability models suggest the occurrence and local-scale cover of B. pertusa is largely determined by climate variables and the foliage projective cover of trees. Based on these results B. pertusa still has considerable capacity to spread and increase in dominance across many areas of Queensland, particularly further west and south of its current range. The introduction and spread history of B. pertusa suggests propagule pressure, traits, climate, land management and cultural perceptions are all key factors implicated in the spread of B. pertusa . Where B. pertusa has become dominant there has been a major shift in lifeform from native perennial tussock species to a grazing tolerant stoloniferous species. To slow this process of ‘lawnification’ we recommend more conservative grazing strategies and strategically selected protected areas to maintain cover of grazing sensitive native tussock grass species.

Modelling climatic suitability for myrtle rust with a widespread host species - Natalie A. Meiklejohn; Timothy L. Staples; Rod J. Fensham (Biological Invasions, 2022)

Spatiotemporal variance of environmental conditions in Australian artesian springs affects the distribution and abundance of six endemic snail species - Renee A. Rossini; Rod J. Fensham; Gimme H. Walter (Aquatic Ecology, 2017)

Structural overshoot of tree growth with climate variability and the global spectrum of drought‐induced forest dieback - Alistair S. Jump; Paloma Ruiz‐Benito; Sarah Greenwood; Craig D. Allen; Thomas Kitzberger; Rod Fensham; Jordi Martínez‐Vilalta; Francisco Lloret (Global Change Biology, 2017)
Ongoing climate change poses significant threats to plant function and distribution. Increased temperatures and altered precipitation regimes amplify drought frequency and intensity, elevating plant stress and mortality. Large‐scale forest mortality events will have far‐reaching impacts on carbon and hydrological cycling, biodiversity, and ecosystem services. However, biogeographical theory and global vegetation models poorly represent recent forest die‐off patterns. Furthermore, as trees are sessile and long‐lived, their responses to climate extremes are substantially dependent on historical factors. We show that periods of favourable climatic and management conditions that facilitate abundant tree growth can lead to structural overshoot of aboveground tree biomass due to a subsequent temporal mismatch between water demand and availability. When environmental favourability declines, increases in water and temperature stress that are protracted, rapid, or both, drive a gradient of tree structural responses that can modify forest self‐thinning relationships. Responses ranging from premature leaf senescence and partial canopy dieback to whole‐tree mortality reduce canopy leaf area during the stress period and for a lagged recovery window thereafter. Such temporal mismatches of water requirements from availability can occur at local to regional scales throughout a species geographical range. As climate change projections predict large future fluctuations in both wet and dry conditions, we expect forests to become increasingly structurally mismatched to water availability and thus overbuilt during more stressful episodes. By accounting for the historical context of biomass development, our approach can explain previously problematic aspects of large‐scale forest mortality, such as why it can occur throughout the range of a species and yet still be locally highly variable, and why some events seem readily attributable to an ongoing drought while others do not. This refined understanding can facilitate better projections of structural overshoot responses, enabling improved prediction of changes in forest distribution and function from regional to global scales.

Tree mortality across biomes is promoted by drought intensity, lower wood density and higher specific leaf area - Sarah Greenwood; Paloma Ruiz‐Benito; Jordi Martínez‐Vilalta; Francisco Lloret; Thomas Kitzberger; Craig D. Allen; Rod Fensham; Daniel C. Laughlin; Jens Kattge; Gerhard Bönisch; Nathan J. B. Kraft; Alistair S. Jump (Ecology Letters, 2017)
Drought events are increasing globally, and reports of consequent forest mortality are widespread. However, due to a lack of a quantitative global synthesis, it is still not clear whether drought‐induced mortality rates differ among global biomes and whether functional traits influence the risk of drought‐induced mortality. To address these uncertainties, we performed a global meta‐analysis of 58 studies of drought‐induced forest mortality. Mortality rates were modelled as a function of drought, temperature, biomes, phylogenetic and functional groups and functional traits. We identified a consistent global‐scale response, where mortality increased with drought severity [log mortality (trees trees −1 year −1 ) increased 0.46 (95% CI = 0.2–0.7) with one SPEI unit drought intensity]. We found no significant differences in the magnitude of the response depending on forest biomes or between angiosperms and gymnosperms or evergreen and deciduous tree species. Functional traits explained some of the variation in drought responses between species (i.e. increased from 30 to 37% when wood density and specific leaf area were included). Tree species with denser wood and lower specific leaf area showed lower mortality responses. Our results illustrate the value of functional traits for understanding patterns of drought‐induced tree mortality and suggest that mortality could become increasingly widespread in the future.

An ecoclimatic framework for evaluating the resilience of vegetation to water deficit - Patrick J. Mitchell; Anthony P. O'Grady; Elizabeth A. Pinkard; Timothy J. Brodribb; Stefan K. Arndt; Chris J. Blackman; Remko A. Duursma; Rod J. Fensham; David W. Hilbert; Craig R. Nitschke; Jaymie Norris; Stephen H. Roxburgh; et al. (Global Change Biology, 2016)
The surge in global efforts to understand the causes and consequences of drought on forest ecosystems has tended to focus on specific impacts such as mortality. We propose an ecoclimatic framework that takes a broader view of the ecological relevance of water deficits, linking elements of exposure and resilience to cumulative impacts on a range of ecosystem processes. This ecoclimatic framework is underpinned by two hypotheses: (i) exposure to water deficit can be represented probabilistically and used to estimate exposure thresholds across different vegetation types or ecosystems; and (ii) the cumulative impact of a series of water deficit events is defined by attributes governing the resistance and recovery of the affected processes. We present case studies comprising Pinus edulis and Eucalyptus globulus , tree species with contrasting ecological strategies, which demonstrate how links between exposure and resilience can be examined within our proposed framework. These examples reveal how climatic thresholds can be defined along a continuum of vegetation functional responses to water deficit regimes. The strength of this framework lies in identifying climatic thresholds on vegetation function in the absence of more complete mechanistic understanding, thereby guiding the formulation, application and benchmarking of more detailed modelling.

The history and fate of the Nubian Sandstone Aquifer springs in the oasis depressions of the Western Desert, Egypt - Owen Powell; Rod Fensham (Hydrogeology Journal, 2016)

Buffel grass and climate change: a framework for projecting invasive species distributions when data are scarce - Tara G. Martin; Helen Murphy; Adam Liedloff; Colette Thomas; Iadine Chadès; Garry Cook; Rod Fensham; John McIvor; Rieks D. van Klinken (Biological Invasions, 2015)

Effect of woody vegetation clearing on nutrient and carbon relations of semi-arid dystrophic savanna - Susanne Schmidt; Rebecca E. Lamble; Rod J. Fensham; Ilyas Siddique (Plant and Soil, 2010)

A morphological cline in Eucalyptus : a genetic perspective - James E. Holman; Jane M. Hughes; Rod J. Fensham (Molecular Ecology, 2003)
The putative hybrid zone between Eucalyptus populnea and E. brownii is examined using morphological and molecular techniques. This species complex displays continuous morphological variation across the study area, which has been previously interpreted as the product of hybridization between allopatric species. A microsatellite analysis indicates that there was little genetic structuring across the morphological cline and only low levels of population differentiation. The nested clade analysis of the J LA+ region of the chloroplast DNA (cpDNA) indicates that the geographical distribution of cpDNA haplotypes is unlikely to be the result of historical hybridization events, and that restricted seed‐mediated gene flow with isolation by distance is responsible for the phylogeographical distribution. A more plausible explanation for the origin and persistence of the morphological cline is that the process of continuous morphological diversification has been promoted by a directional selection gradient. This study addresses species status within Eucalyptus and the belief that hybridization is widespread and is an important process in the group's evolution.